Enhancing EFL reading comprehension and motivation through interactive gamified learning in Indonesia - Iswanto, Achmad Rahman; Sabat, Yuliyanto; Wafiroh, Laili Hibatin (Jurnal Inspirasi Pendidikan, 2026)
Teaching English as a Foreign Language (EFL) in Indonesian secondary schools continues to face major challenges due to students' weak reading comprehension. This study aims to evaluate the effectiveness of the Wayground gamified learning platform in improving reading comprehension and learning motivation among Indonesian secondary students of English as a Foreign Language (EFL). This study addresses the critical challenges of low literacy rates and high reading anxiety in the digital age. A quasi-experimental design was used, involving 60 tenth-grade students at SMAN 2 Sampang, who were divided into an experimental group using Wayground and a control group using traditional teacher-centered instruction. Data were collected over six weeks using a 20-item reading comprehension test and a modified Instructional Materials Motivation Survey (IMMS) based on Keller's ARCS model. Descriptive and inferential statistics, including the Mann-Whitney U test and the Wilcoxon Signed-Rank test, were used for data analysis. The results showed that students in the experimental group significantly outperformed the control group, achieving a post-test average of 85.43 compared to 71.07. In addition, student motivation in all ARCS dimensions reached high levels, with the highest satisfaction scores. It was concluded that Wayground served as a powerful catalyst, transforming passive reading activities into student-centered, interactive experiences while effectively mitigating cognitive fatigue. These findings indicate that integrating Wayground's interactive, gamified learning into the curriculum provides a fundamental basis for promoting learner autonomy and improving literacy outcomes in 21st-century education.